REPRESENTASI DUDA DALAM FILM SEJUTA SAYANG UNTUKNYA - Rohim, Syaiful; Afaf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
This study describes how is the representation of widower as a single parent which is described through media content, namely Sejuta Sayang Untuknya Movie. By using research methods and qualitative content analysis, the results of the analysis of this study is related to the theory of media content, where the scenes in the film are formed by film makers to provide shows that represent the reality of society, where the actor is portrayed as a father who always shows affection for his daughter by speaking softly, giving attention, being a good friend to his daughter and prioritizing his daughter's needs.